2003
DOI: 10.1074/jbc.m303428200
|View full text |Cite
|
Sign up to set email alerts
|

RGD-containing Peptides Activate S6K1 through β3 Integrin in Adult Cardiac Muscle Cells

Abstract: The enzyme p70S6 kinase (S6K1) is critical for cell growth, and we have reported its activation during cardiac hypertrophy. Because cardiac hypertrophy also involves integrin activation, we analyzed whether integrins could contribute to S6K1 activation. Using adult feline cardiomyocytes, here we report that integrin-interacting Arg-Gly-Asp (RGD) peptides activate S6K1 as observed by band shifting, kinase activity and phosphorylation at Thr-389 and Thr-421/Ser-424 of S6K1, and S6 protein phosphorylation. Pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 63 publications
4
40
0
Order By: Relevance
“…RAD001 triggered b3 up-regulation may then reflect an undesired feedback loop which counteracts the adhesion diminishing properties of this compound. In fact, studies on cardiomyocyte cultures have indicated that stimulation of b3 integrins reactivates mTOR related pathways [29], the process of which has been correlated to reduced drug efficacy [30]. This is corroborated by our own findings revealing a superior anti-tumor effect of VPA in both the tumor-endothelial coculture assay and the tumor matrix system, compared to RAD001.…”
Section: Discussionsupporting
confidence: 52%
“…RAD001 triggered b3 up-regulation may then reflect an undesired feedback loop which counteracts the adhesion diminishing properties of this compound. In fact, studies on cardiomyocyte cultures have indicated that stimulation of b3 integrins reactivates mTOR related pathways [29], the process of which has been correlated to reduced drug efficacy [30]. This is corroborated by our own findings revealing a superior anti-tumor effect of VPA in both the tumor-endothelial coculture assay and the tumor matrix system, compared to RAD001.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, stimulation of h3 integrin with Arg-Gly-Asp peptide in isolated adult cardiomyocytes triggers activation of c-SRC accompanied by binding to p130CAS and phosphorylation of FAK Tyr925 [34]. In addition, activation of p70S6 kinase, via mTOR, MEK/ERK, and phosphatidylinositol 3-kinase is also promoted by Arg -Gly-Asp stimulation of h3 integrin in cardiomyocytes [35]. While these studies clearly indicate an important role of h3 integrin in isolated cardiomyocytes, its involvement in cardiac hypertrophy in vivo remains to be clarified.…”
Section: Integrin-linked Molecular Machinery Triggering Signal Transdmentioning
confidence: 93%
“…The increase in translational capacity is supported by our observation of FN-induced expression of ribosomal protein genes, resulting in the highest z-score of the pathways examined (Table 3). It is known that hypertrophy and integrin activation increases the translational efficiency of ribosomal protein mRNAs (3,54). Therefore, it is likely that the abundance of ribosomal proteins increases during hypertrophy due to increased transcription and increased translation.…”
Section: Discussionmentioning
confidence: 99%